Avaliação clínica de um enxaguatório a base de dióxido de cloro na redução dos compostos sulfurados voláteis - Soares, Léo Guimarães (2009)
The clinical treatment of the bad breath began, basically, with the mechanical methods based in the first tongue´s cleaner, inciting the researches to develop studies involving chemical substances. The subject of the present study is to evaluate mouthrinses in the reduction of the sulfur compounds, when used for mouthwash, in the induced halitosis. The study consisted in a randomized evaluation, double-blind, crossover, and placebo-controlled of eleven healthy volunteers, where the halitosis was induced through the rinse of L-cysteine ( 6mMol – pH 7.2 ). Four mounthrinses were used: test ( on the basis of chlorine dioxide ), placebo ( negative control ), cetylpyridinium chloride and gluconatechlorhexidine to 0,12% ( positive control ). To measure the levels of volatile sulfur compounds ( VSC ), a Sulfide Monitor wasused. For each mounthrinses, six measurements were made on participants: initial, post-cysteine, post-rinse after one hour, after two hours and after three hours. All participants used the four mouthrises, and had washout period of at less than on week between the monthwashes of the solutions. After the values measured by sulfide monitor in parts per billion ( ppb ), the reduction rate of VSC levels was found, wichwas subtraction of values post-rinse, after one hour, after two hours, after three hours, values by their post cysteine. The amount of reduction in VSC was given in percentage. In all of the periods of time, the reduction rate of mounthrinse test was superior to placebo and cetylpyridium and was similar to chlorhexidine, both being statistically superior to placebo and cetylpyridinium. Based on results, we can conclude that the mounthrinses test based on chlorine dioxide was able to reduce levels of volatiles sulfur compounds for a period of up to three hours.